2003
DOI: 10.1038/ng1222
|View full text |Cite
|
Sign up to set email alerts
|

Trans-acting regulatory variation in Saccharomyces cerevisiae and the role of transcription factors

Abstract: Natural genetic variation can cause significant differences in gene expression, but little is known about the polymorphisms that affect gene regulation. We analyzed regulatory variation in a cross between laboratory and wild strains of Saccharomyces cerevisiae. Clustering and linkage analysis defined groups of coregulated genes and the loci involved in their regulation. Most expression differences mapped to trans-acting loci. Positional cloning and functional assays showed that polymorphisms in GPA1 and AMN1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

52
603
3
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(665 citation statements)
references
References 39 publications
52
603
3
7
Order By: Relevance
“…Recently, a yeast intercross study showed a notable absence of over-represented gene categories near trans eQTLs, suggesting no hierarchy of functional classes 36 . We investigated whether the same conclusion was true for our radiation hybrid data.…”
Section: Functional Categorization Of Trans Ceqtlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a yeast intercross study showed a notable absence of over-represented gene categories near trans eQTLs, suggesting no hierarchy of functional classes 36 . We investigated whether the same conclusion was true for our radiation hybrid data.…”
Section: Functional Categorization Of Trans Ceqtlsmentioning
confidence: 99%
“…The absence of Gene Ontology category enrichment near trans ceQTLs in the yeast intercross study 36 may represent lack of naturally occurring polymorphisms for genes at network hubs. This relative deficiency might arise because of selective pressure.…”
Section: Functional Categorization Of Trans Ceqtlsmentioning
confidence: 99%
“…Following the ''gold rush'' ushered in by the sequencing of the S. cerevisiae genome, efforts are being made to revisit this natural diversity. Phenotypic analyses of diverse yeast strains [1,2] and the application of microarray technology to the analysis of allelic variation [3][4][5][6][7][8] and population genetic variation in gene expression [9][10][11] are providing new insights into the ecology and diversity of the species. Such analyses should also be applicable to the elucidation of pathways that face strong diversifying selection, such as those governing uptake and metabolism of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…(cis regulation refers to the control of expression by the gene itself whereas trans regulation refers to the influence of the genetic background.) Many studies have addressed this question at various levels of divergence (1)(2)(3)(4)(5)(6)(7)(8)(9). For example, one may measure the expressions of two alleles at the locus of interest in a common genetic background (usually F 1 s) (1,2,5).…”
mentioning
confidence: 99%